NATIONAL INTEGRATION IN THE ERA OF GLOBALIZATION: THE CHALLENGES OF MULTICULTURALISM AND THE EFFORTS OF INDONESIAN YOUTH - Bambang Yuniarto; Nadia Ulfa; Aulia Gahalis; Muhammad Habil; Adhitya Refki Priyadi (Adisam Publisher, 2025)
This study aims to analyze the challenges of Indonesia’s national integration in the era of globalization, which has become increasingly complex due to multicultural dynamics and global influences on national values, identity, and solidarity. The main problem addressed is how Indonesia’s diverse ethnic, cultural, and religious backgrounds may lead to potential disintegration if not balanced by strong national awareness. This research employs a qualitative approach using a literature study method that examines theories of social integration, globalization, and the role of youth in national development. Data were gathered from academic sources such as journals, books, policy reports, and previous studies. The findings reveal that globalization has two major impacts: first, it opens cross-cultural interactions that enrich national perspectives; second, it increases challenges to national identity due to global cultural penetration. In this context, Indonesian youth play a vital role as agents of national integration through social innovation, digital literacy, and the strengthening of tolerance and cooperation values. Efforts to sustain national integration amid multiculturalism require synergy between government policy, educational institutions, and youth movements to build a collective consciousness of unity in diversity.